Evolution and clinical implications of right ventricular dysfunction in ischemic cardiomyopathy with or without coronary artery bypass surgery. (3rd October 2022) - Zhou, Z; Liang, M; Jian, B; Fu, G; Wu, Z
Abstract: Background: The Surgical Treatment of Ischemic Heart Failure (STICH) trial demonstrated that coronary artery bypass grafting (CABG) provides additional survival benefits to patients with ischemic cardiomyopathy. However, it remains unclear whether this benefit is affected by preoperative right ventricular (RV) function and how post-therapeutic evolution of RV function influences long-term outcomes. Purpose: We sought to investigate the implications of baseline RV function on therapeutic decision-making in patients with ischemic cardiomyopathy, and to evaluate the prognostic implications of post-therapeutic evolution of RV function. Methods: Patients with available baseline echocardiographic RV function assessed by experienced Echocardiography Core Laboratory physicians were included from the hypothesis 1 of the STICH trial. The primary outcome was long-term all-cause mortality. Results: A total of 1042 patients were included, among them 757 (72.7%) had normal RV function, 143 (13.7%) mild right ventricular dysfunction (RVD), and 142 (13.6%) moderate to severe RVD. After a median follow-up of 9.8 years, patients with RVD had a higher risk of all-cause mortality compared with patients with normal RV function [mild RVD: adjusted hazard ratio (aHR) 1.32; 95% confidence interval (CI) 1.06–1.64; moderate to severe RVD: aHR, 1.74; 95% CI 1.39–2.18]. Although no significant interaction was detected between RVD degree and treatment allocation (P for interaction = 0.399), a gradually decreasing survival benefit associated with CABG was observed among patients with normal RV function (aHR: 0.79; 95% CI: 0.65–0.96), mild RVD (aHR: 0.85; 95% CI: 0.56–1.29), and moderate to severe RVD (aHR: 0.97; 95% CI: 0.67–1.43). Among 746 patients with available RV function assessed at baseline and post-therapeutic 4-month follow-up, there was a gradient of increasing risk for all-cause mortality across patients with consistent normal RV function, recovery of RVD (aHR: 1.20; 95% CI: 0.88–1.64), newly developed RVD (aHR: 1.59; 95% CI: 1.18–2.14), and consistent RVD (aHR: 2.06; 95% CI: 1.60–2.67). Independent predictors of RVD recovery included baseline left ventricular ejection fraction (per 1-percent increment, adjusted odds ratio: 1.04; 95% CI: 1.00–1.09) and mitral regurgitation ≥ grade 2 (adjusted odds ratio: 0.42; 95% CI: 0.21–0.84). Conclusions: Baseline RVD was associated with an increased risk of long-term mortality in patients with ischemic cardiomyopathy, and adding CABG to medical therapy might provide limited survival benefits in patients with moderate to severe RVD. A gradient of increasing risk for mortality was observed across different categories of RV function evolution, which emphasizes the necessity of pre- and post-therapeutic RV assessment for prognostic evaluation. Funding Acknowledgement: Type of funding sources: None.